Biomedical potential of cyanobacteria and algae - Ughy, Bettina; Nagy, Csaba István; Kós, Péter B. (Acta Biologica Szegediensis, 2015)
Cyanobacteria have appeared on the primordial Earth over three billion years ago and still thrive in most habitats. These photosynthetic microbes have remarkable genetic plasticity and variability and have evolved an amazing arsenal of biochemical pathways that exert defence mechanisms and produce metabolites unique to them. By forming plastids, endosymbiont cyanobacteria contributed to the development of plants. Algae, the simplest plants, thrive in similar habitats and face the same challenges of the ever changing environment as cyanobacteria; and they have maintained similarity to them, with respect to production of unique metabolites and utilizing unique pathways. The exploration of these natural compounds and the biochemical pathways leading to their production provide excellent tools in fighting some major challenge that mankind needs to face in our days. In this contribution we briefly list the benefits that the genetics of these microbes and the produced compounds can offer, with emphasis on possible medical relevance. We mention applications in basic science, industry and agriculture, and list the potentials in medical drug development, therapy and nutrition of some enzymes, polysaccharides, polyphenols, pigments, peptides and lipids, among others, in the current state of the world-wide research on the topic.